QUANTITATIVE ESTIMATION OF CAPTOPRIL IN PHARMACEUTICALS: A SPECTROPHOTOMETRIC APPROACH WITH O-CHLORANIL (Academicia Globe: Inderscience Research, 2023)
A novel, easy, quick, and precise spectrophotometric method for the estimation of captopril in pure form and in pharmaceutical preparations is proposed by a charge transfer (CT) complex formation